2011
DOI: 10.1111/j.1365-294x.2011.05179.x
|View full text |Cite
|
Sign up to set email alerts
|

Niche segregation and genetic structure of Campylobacter jejuni populations from wild and agricultural host species

Abstract: Bacterial populations can display high levels of genetic structuring but the forces that influence this are incompletely understood. Here, by combining modelling approaches with multilocus sequence data for the zoonotic pathogen Campylobacter, we investigated how ecological factors such as niche (host) separation relate to population structure. We analysed seven housekeeping genes from published C. jejuni and C. coli isolate collections from a range of food and wild animal sources as well as abiotic environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
145
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(157 citation statements)
references
References 26 publications
6
145
0
Order By: Relevance
“…The analysis of the 52 rMLST (19) loci confirmed that MLST clonal complexes were genealogically coherent and it provided further information in two respects, (i) improved resolution within clonal complexes, enabling resolution of groups with greater discrimination than achieved with MLST, and (ii) information on the relationships among a number of clonal complexes, for example, the ST-21, ST-48, and ST-206 clonal complexes. The latter clonal complexes typically are isolated from livestock as well as from human patients and include Campylobacter strains that are adapted to the agricultural environment (29) (Fig. 2).…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of the 52 rMLST (19) loci confirmed that MLST clonal complexes were genealogically coherent and it provided further information in two respects, (i) improved resolution within clonal complexes, enabling resolution of groups with greater discrimination than achieved with MLST, and (ii) information on the relationships among a number of clonal complexes, for example, the ST-21, ST-48, and ST-206 clonal complexes. The latter clonal complexes typically are isolated from livestock as well as from human patients and include Campylobacter strains that are adapted to the agricultural environment (29) (Fig. 2).…”
Section: Discussionmentioning
confidence: 99%
“…Among wild birds, specific bird species most often harbor their own Campylobacter lineages (8,9). However, in agricultural animals, although there are host-associated lineages that are largely restricted to chickens or to ruminants, some of the most abundant lineages are found at high frequencies in chickens, cattle, and humans with food poisoning (8). This multihost lifestyle is curious because of the challenges of colonizing organisms with such distinct gastrointestinal tracts, diets, immune systems, and body temperatures.…”
mentioning
confidence: 99%
“…The characterization of large numbers of C. jejuni and C. coli isolates from diverse sources and locations by multilocus sequence typing (MLST) has shown that there is genetic differentiation among sequence types (STs) associated with different hosts (8). Among wild birds, specific bird species most often harbor their own Campylobacter lineages (8,9).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Introgression of C. jejuni genes appears to be limited to clade 1, which comprises organisms mostly associated with poultry and human disease. Clades 2 and 3 are mostly found in wild animals and environmental sources, are not introgressed with C. jejuni genes, and are rarely associated with human disease (Sheppard et al, 2008;Sheppard et al, 2011a;Sheppard et al, 2013a). By contrast, C. jejuni comprises a large number of genetic types, with widespread evidence for recombination throughout the species.…”
Section: Campylobacter Sppmentioning
confidence: 99%